Research Note—A Model of Conflict, Leadership, and Performance in Virtual Teams - Wakefield, Robin L.; Leidner, Dorothy E.; Garrison, Gary (Information Systems Research, 2008)
Organizations in many different industries employ virtual teams in a variety of contexts, including research and development, customer support, software development, and product design. Many virtual teams are geographically and culturally dispersed in order to facilitate around-the-clock work and to allow the most qualified individuals to be assigned to a project team. As such dispersion increases, virtual teams tend to experience greater and more diverse conflict compared to co-located teams. Since the dynamics of virtual team leadership are not yet well understood, research that examines how team leaders alleviate threats to team cohesion and provide strategies for conflict resolution makes significant contributions to the literature. Our study uses a survey-based methodology to examine the perceptions of 159 virtual team members employed by a large U.S. telecommunications corporation and five Korean firms involved in construction, finance, business consulting, sales, and distribution. The study integrates the dynamic model of conflict in distributed teams with the behavioral complexity in leadership theory to investigate the roles that virtual team leaders must effectively employ to reduce various forms of virtual team conflict. Our findings indicate that communication technologies are effective in reducing task conflict; however, the team leader may also mitigate task conflict by assuming the role of monitor. Likewise, process conflict may be abated in the virtual team as the leader performs coordinator activities. An effective virtual team leader exhibits specific roles to manage different types of conflict and the leader's response to conflict plays an important part in virtual team success.